The Importance of Demand Forecasting Method and Material Requirement Planning (MRP) for in Vitro Fertilization Products: Case Study of PT. XYZ - Najamudin, Muhammad Zaim; Handayati, Yuanita (Journal of Business and Management, 2016)
Abstract. Having a balanced ratio between supply and demand is important in running business. Hence, to have a balanced ratio of supply and demand, a firm could control its supply input in order to adapt its supply with the demand level. When the level of mismatch between supply and demand are very high, it will create subsequent level of inventory. Which, is considered as waste in the practices of lean operations. Thus, to eliminate the over-amount of stocks or inventory, forecasting the demand level for products could be the response. However, the outcome of the forecasting method would not stand a chance minimizing all the operational obstacles of a firm if it does not have any support. Material Requirement Planning (MRP) can provide the considerations of lead time. This research conducted a case study in PT XYZ, which is a distributor of In-Vitro Fertilization (IVF) technology supplies in Indonesia. This company has experienced problems with overstocks and losses due to the problem of mismatch between supply and demand.Â Moreover, the firm has not applied a methodized demand forecasting system. Thus, this researchâ€™s aim is to determine the suitable forecasting method for the firm. Besides the forecast method, this research also enhances the application of MRP to provide a better understanding of procurement decisions. Taking the positives from this paper will hope to add up to the learning curve of a developing company with a comparable business model in medical or other industries with similar characteristics.Keywords: demand forecasting, MRP, In-Vitro Fertilization, medical technology, case study.